Evaluation of the Screening Performance of Ultrasonographic Abdominal Circumference and Estimated Fetal Weight in Predicting Small for Gestational Age Newborns - Dal, Yusuf; Akkus, Fatih; Karagun, Sebnem; Nessar, Ahmet Zeki; Karaca, Sefanur Gamze; Aytan, Hakan; Coskun, Ayhan (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVES: We aimed to evaluate the screening performance of estimated fetal weight (EFW) and abdominal circumference (AC) measurements in predicting newborns with birth weight (BW) less than the 10th percentile for birth age (BW <10p). STUDY DESIGN: Three hundred thirty-one pregnant women who met the inclusion and exclusion criteria were included in the study. The groups were divided into two groups: those diagnosed with FGR (FGR group) and those not diagnosed (non-FGR)after the 32nd week of gestation. Demographic and obstetric histories, ultrasonographic and clinical features, and neonatal outcomes of the groups were recorded, and comparisons between the groups were conducted. The screening performances of AC and EFW were compared for predicting newborns with BW<10p and assessing neonatal outcomes. RESULTS: AC or EFW measures below 10% (AC<10p or EFW<10p) demonstrated the highest screening performance for BW<10p, with 91.7% sensitivity and 91% specificity. AC<10p demonstrated the highest performance in predicting neonatal intensive care unit (NICU) admission, with 75.9% sensitivity and 89.1% specificity. For neonates with a 5-minute APGAR score of less than 7, AC<10p or EFW<10p had 88.2% sensitivity and 69.7% specificity. CONCLUSION: This study shows that AC and EFW measurements can be used together or separately to predict newborns who are small for their gestational age (SGA). Using values below 10% of either AC or EFW together gives the best results in terms of sensitivity and specificity.